Cómo puedo probar que $$\frac{(-1)^n}{n+(-1)^n\sqrt{n+1}}=\frac{(-1)^n}{n} +\mathcal{O}\left(\dfrac{1}{n^{3/2}}\right)\tag{$*$}$$
utilizando el siguiente método :
tenga en cuenta que : $(1+x)^{\alpha}=1+\alpha x+\mathcal{O}(x^{2})\quad ( x\to 0) $
\begin{align} \frac{(-1)^n}{n+(-1)^n\sqrt{n+1}}&=\frac{(-1)^n}{n} \left(1+\frac{(-1)^n\sqrt{n+1}}{n} \right)^{-1}\\ &\text{since } \sqrt{n+1}\sim \sqrt{n} \text{ then } \lim_{n\to+\infty}\frac{\sqrt{n+1}}{n}=0 \\ &\sim \frac{(-1)^n}{n}\left(1+\frac{(-1)^n\sqrt{n}}{n} \right)^{-1}\\ &= \frac{(-1)^{n}}n\left(1+\mathcal{O}\left( \frac{(-1)^n\sqrt{n}}{n}\right) \right)\\ &= \frac{(-1)^n}{n}+\mathcal{O}\left( \dfrac{(-1)^{2n}\sqrt{n}}{n^2}\right) \\ &=\frac{(-1)^n}{n}+\mathcal{O}\left(\dfrac{1}{n^{3/2}}\right) \end{align}
- ESTOY en lo cierto ?